STUDENT’S PERCEPTION ON MOBILE LEARNING: THE INFLUENCING FACTORS - Anushia Chelvarayan; Chee Jia En; Yeo Sook Fern; Hazlaili Hashim (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Mobile learning has become the most popular way of transporting information and the number of users has been rapidly increasing all over the world. Most importantly, students, these days can be defined as members of the digital native or network generation, born in the digital era while interacting with digital technology since childhood. Mobile devices have gradually become more popular around the world. Due to their popularity, the education sector has considered mobile learning (M-learning) technologies as pedagogical tools for users to be able to use their devices for self-learning anytime and anywhere. Therefore, this study examines the factors affecting students’ perception of mobile learning. Several types of research show University professors are adopting mobile learning for discussion meetings in order to help students in academic learning and through effective connection and collaboration inside and outside the classroom. The theoretical foundations for this study are the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT). A total of 200 respondents from a private university in Malaysia participated in this research. Samples were selected using convenience sampling and the respondents answered the questionnaire via Google form and paper and pencil method. A nominal scale and Five-point Likert scale was used to design the questions in the questionnaire. Data analysis methods used in this research were Descriptive Analysis, Reliability Analysis, and Multiple Regression Analysis. The data collected and also information in this research are highly beneficial and valuable to students, supervisors, academics, researchers, learning institutions, and the government as we are able to gauge and understand the factors influencing students’ perception of mobile learning. However, there are some limitations as this research does not reflect the actual student population in tertiary education in Malaysia and it only focuses on four variables i.e. performance expectancy, effort expectancy, social influence, and quality of service. There are several possibilities for future researches whereby one can focus more on other influencing factors such as pervasive technology usage, tech-savvy future generations, convenience, and many more.